An analysis on Artificial Intelligence - Sen, Pawan; Kumawat, Shalini (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network; Vol 4 No 1 (2020): Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2021)
Artificial intelligence is exhibited by artificial entity. The inventor of the artificial intelligence is “John Mcmarthy”. We have to intelligence about artificial intelligence goals like - logical reasoning, planning, machine learning. And also discuss about a machine learning and its applications like – financial services, marketing and sales, government healthcare etc. How to cite this article: Sen P, Kumawat S. An Analysis on Artificial Intelligence. J Adv Res Appl Arti Intel Neural Netw 2020; 4(1): 10-12.